Cortex Fraxini (Qingpi) Protects Rat Pheochromocytoma Cells against 6-Hydroxydopamine-Induced Apoptosis - Jing-Jie Li; Shi-Ya Zhou; Huan Zhang; Kim-Hung Lam; Simon Ming-Yuen Lee; Peter Hoi-Fu Yu; Shun-Wan Chan (Parkinson's Disease)
Parkinson’s disease (PD) is a chronic neurodegenerative disorder having close relationship with oxidative stress induced by reactive oxygen species (ROS). Cortex Fraxini (QP) is a kind of traditional Chinese medicinal herb with antioxidant properties. It may be a potential candidate for preventing the development of chronic neurodegenerative diseases. Thus, the key objective of the current study was to investigate the neuroprotective effect of QP water extract on 6-hydroxydopamine (6-OHDA) induced apoptosis in rat pheochromocytoma (PC12) cells. It was found that QP water extract possesses strong antioxidant property with SC50 = 0.15 mg/mL. Total phenolic content of QP water extract was found to be 200.78 ± 2.65 mg GAE/g. QP water extract’s free radical scavenging capacity was demonstrated by reversing the increased level of intracellular ROS induced by 6-OHDA, using 2′,7′-dichlorodihydrofluorescein diacetate. Moreover, QP water extract (0.5 mg/mL) could remarkably increase the viability of PC12 cells treated with 6-OHDA. The protective effect of QP water extract was found to be via inhibiting MEK/ERK pathway and reversing PI3-K/Akt/GSK3β pathway. The current results suggest that QP might be a potential candidate for preventing the development of neurodegenerative diseases, such as PD.